Fault slip of the 2022 Mw6.7 Menyuan, China earthquake observed by InSAR, and its tectonic implications - Yang, Yuetong; Song, Xiaogang; Gong, Wenyu; Qu, Chunyan (Frontiers in Earth Science, 2023)
The ascending and descending Sentinel-1A satellite data are used to investigate the coseismic slip model of the 2022 Mw6.7 Menyuan, Qinghai, China, earthquake. The optimal slip model indicates that this event ruptured two fault segments. The main rupture concentrated on the western Lenglongling (LLL) fault with a purely left-lateral striking-slip motion. A small part of eastern Tuolaishan (TLS) fault section has also been ruptured, and the motion on it is mainly oblique slip, with obvious thrust component. Combined with the rupture characteristics of historical events, GPS velocity map, and slip rate studies, we suggest that the TLS–LLL fault junction is a demarcation point where the deformation partitioning pattern has changed. Along the whole LLL segment, the oblique convergence has completely partitioned into slip on the purely strike-slipping LLL fault and thrusting faults in the north. Instead, the TLS fault segment still accommodates a fraction of compressional shortening, which compensates for the discrepancy on left-lateral slip rate between the LLL fault and TLS fault. Such transformation in strain partitioning pattern is likely to be determined by geometric relationship between fault strike and the direction of regional block movement.